Handbook of research on computer mediated communication / vol.2 - Kelsey, Sigrid; St. Amant, Kirk, 1970- (Hershey, PA : Information Science Reference, 2008)
"This book provides academics and practitioners with an authoritative collection of research on the implications and social effects computers have had on communication. With 65 chapters of innovative research compiled in this comprehensive reference source, this handbook of research is a must-have addition to every library collection"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Computer-assisted instruction; Communication and technology; Information technology -- Social aspects